Analysis of Financial Literacy, Financial Capability and Financial Ease on the Interest of Digital Financial System Users in Paying for Mangrove Forest Tourism Entrance Tickets in Pantai Cermin - Maya Syaula; Geby Citra Ananda; Fachrid Wadly; Andrian Syahputra (Yayasan Multidimensi Kreatif, 2024)
Digitalization in the payment system has become an important need in the modern era, especially in supporting the tourism sector. This study aims to analyze the influence of knowledge, ability, and convenience on the interest in using digital finance on the entrance ticket payment system in the Pantai Cermin Mangrove Forest tourism. A quantitative approach was used in this study by involving 40 respondents as a sample, which was selected using the purposive sampling technique. Data were collected through a Likert scale questionnaire and analyzed using the multiple linear regression method with the help of SPSS. The results showed that partially, the knowledge variable had a significant positive influence on interest in using digital finance (p-value = 0.002, β = 0.320). Ability variables also had a significant positive effect (p-value = 0.005, β = 0.289). The convenience variable was the dominant factor with the largest significant positive influence (p-value = 0.001, β = 0.395). Simultaneously, these three variables have a significant effect on interest in the use of digital finance with a value of F-count = 19,763 and p-value = 0.000. The determination coefficient (R2) value of 0.625 shows that 62.5% of the variation in interest in use can be explained by knowledge, ability, and convenience, while the rest is influenced by other factors outside the research model.